Pengaruh Penggunaan Limbah Ampas Te Terhadap Pertumbuhan Tanaman Pakcoy (Brassica Rapa L) dengan Menggunakan Media Hidroponik - Aresi, Friskila Atriani; Ulfa, Nurul Alia; prabawati, Ratna (STKIP HARAPAN BIMA, 2025)
The study aims to determine the effect of tea dregs waste on the growth of pak choy plants. The study was conducted using quantitative methods and a Completely Randomized Design (CRD) with four tea dregs dosage treatments, namely 0 grams, 40 grams, 60 grams, and 80 grams per liter of nutrient water, each with three replications. The parameters observed included plant height, number of leaves, and fresh weight of the plant. Data were collected using an observation sheet, then analyzed using ANOVA at a significance level of 5 percent, followed by Duncan's test to determine significant differences between treatments. The results showed that the provision of tea dregs waste had a positive and significant effect on the growth of pak choy (p 0.05). The 80 gram treatment (P3) produced the best growth with an average plant height of 6.3 cm, number of leaves 7.1 strands, and fresh weight 7.4 grams. Increasing the dose of tea dregs increased the availability of macronutrients such as nitrogen, phosphorus, and potassium, thereby supporting photosynthetic activity, vegetative tissue formation, and increasing plant biomass. Despite showing positive results, the use of tea dregs in this study served as a nutritional supplement and cannot fully replace commercial hydroponic nutrients.